Morphological characteristics of atheromatous plaque at carotid bifurcation: Analysis by B-mode real-time ultrasonography - Kojima, Gihei; Kawata, Hajime; Shimizu, Yoji; Yamada, Yoshio; Sueyoshi, Kenji (Japanese Journal of Stroke, 1984)
B-mode real-time ultrasonsgraphy using a linear array electronic scanner with 5 MHz transducer was employed to image atheromatous plaque in the carotid bifurcations of one hundred and eighty three patients with cerebral infarctions, transient ischemic attacks (TIA), diabetes mellitus (DM), hyperlipidemia, and hypertension. In twenty nine patients with cerebrovascular diseases, forty nine carotid arteriographies were performed. The quality of the carotid sonograms were classified to eight categories, i.e., type 0; normal, type I; tiny plaque (diameter below 2 mm), type IIa; bow shaped plaque with smooth surface, type IIb; bow shaped plaque with irregular surface, type IIIa; flat and rectangular plaque with smooth surface, type IIIb; flat and rectangular plaque with irregular surface, type IV; nodular plaque and type V; obstruction. In comparison with arteriography, for detection of normal vessels, stenotic lesions and obstructions, sonographic accuracy was 80%, 100% and 67% respectively. The detection rate of carotid plaque in each disease was as follows; 67% in cerebral infarction, 73% in TIA, 50% in DM, 45% in hyperlipidemia, 32% in hypertension and in 7% in healthy controls. In healthy controls and patients with hypertension, carotid plaques consited of type 0 and type IIa. In patients with DM and hyperlipidemia, type IIIa and type IIa was the most noticeable respectively. In cotrast to findings in subjects who had no strokes, carotid arteries perfusing diseased hemispheres in patients with cerebral infarction and TIA had plaques of type V and IV and plaques with irregular surfaces predominantly. These data suggested that non-invasive detection of morphological characteristics of carotid plaques could be of considerable value in the assessment of severity of macroangiopathy in patients with stroke prone diseases and in the management of patients with cerebrovascular diseases.